Effect of Addition of NaCl Salt on Extraction of Essential Oil from Lemongrass Leaves by Microwave Hydro-Distillation Method - Fenni Suryanti; Lailatul Qadariyah; Mahfud Mahfud (Universitas Gadjah Mada, 2023)
Essential oils are compounds extracted from plants and obtained by distillation. Indonesia has many kinds of plant commodities for essential oil production. Among the essential oils that have not been developed in Indonesia is citronella oil which can be extracted from the lemongrass plant this research, we develop Microwave Hydro-Distillation (MHD) method has several advantages over conventional distillation methods: shorter time, higher oil quality and yield. This research proposes to extract citronella oil from lemongrass leaves using the MHD method using aquadest and NaCl solution addition. Operating variables are extraction time (20–180 min), material size (0.5, 1.0, and 1.5 cm), feed-to-solvent ratio (0.1; 0.15; and 0.2 g/mL), and microwave power (300, 450, and 600 watts). The essential oil results are analyzed by GC-MS analysis, specific gravity, refractive index, and solubility. The results showed that it increased with extraction time followed by almost constant conditions, tended to decrease with increasing feed-to-solvent ratio, and increased yield with increasing microwave power. The results from the GC-MS analysis, the active substance content of geraniol was 46.61% and citronellal 5.62%. Additional salt in this method is a green and clean essential oil extraction.